Reprogramming of Root Cells during Nitrogen-Fixing Symbiosis Involves Dynamic Polysome Association of Coding and Noncoding RNAs - Traubenik, Laura Soledad (2020)
Translational control is a widespread mechanism that allows the cell to rapidly modulate gene expression in order to provide flexibility and adaptability to eukaryotic organisms. We applied translating ribosome affinity purification combined with RNA sequencing to characterize translational regulation of mRNAs at early stages of the nitrogen-fixing symbiosis established between Medicago truncatula and Sinorhizobium meliloti. Our analysis revealed a poor correlation between transcriptional and translational changes and identified hundreds of regulated protein-coding and long noncoding RNAs (lncRNAs), some of which are regulated in specific cell types. We demonstrated that a short variant of the lncRNA Trans-acting small interference RNA3 (TAS3) increased its association to the translational machinery in response to rhizobia. Functional analysis revealed that this short variant of TAS3 might act as a target mimic that captures microRNA390, contributing to reduce trans acting small interference Auxin Response Factor production and modulating nodule formation and rhizobial infection. The analysis of alternative transcript variants identified a translationally upregulated mRNA encoding subunit 3 of the SUPERKILLER complex (SKI3), which participates in mRNA decay. Knockdown of SKI3 decreased nodule initiation and development, as well as the survival of bacteria within nodules. Our results highlight the importance of translational control and mRNA decay pathways for the successful establishment of the nitrogen-fixing symbiosis.